Life-cycle of internet trolls - Jussinoja, Terho (2018)
This paper is a master’s thesis about internet trolls and trolling with the main goal of finding what is the life-cycle of internet trolls. In other words, how a person becomes a troll, how their trolling evolves, and how does trolling stop. Trolling definitions are also examined to see whether they are adequate. This thesis also covers the current state of research done on trolling, with the emphasis on literature that is relevant to the life-cycle of a troll. The literature will also be evaluated against the results from this study. Past research on trolling is quite scarce when comparing to the multiple topics it holds, suggesting that the scientific understanding of internet trolls is still less than ideal. Most of the previous studies have not been able to utilize trolls’ views, whereas this study only uses commentary from trolls. This study was conducted using a qualitative research method, thematic analysis, and used three different methods for data collection. Trolling has become more commonplace in recent years and it has been claimed to be a formidable problem for civil discourse on the internet and therefore deserves better insight on the matter. Media accounts, literature, and public opinions rarely match when it comes to trolling. This shows that there is plenty of confusion and misunderstandings on the topic. By discovering the reasons why an individual decides to troll, and how they decide to stop, there can be better technological solutions developed that might discourage people to start trolling or encourage them to stop.